A comparison of virtual and in person delivery of a full meal replacement program for obesity - Matthew Skeldon; David Harris; Robert Dent; Judy Y. Shiau (Wiley, 2024)
Abstract Objective Full meal replacement (FMR) Intensive Lifestyle Interventions (ILI) have been used for weight management. However, predictors of efficacy with these programs are less clear. The primary objective was to assess weight loss predictors in a community‐based FMR ILI program. A secondary objective was to determine if weight loss was different between virtual and in person ILI. Methods This was a retrospective cohort study involving 234 patients who started the program between 1 January 2016 and 3 March 2021. In the 24‐week program, patients spent 12 weeks on FMR and then transitioned back to food for the remainder, with weekly follow up with a physician and group sessions with a dietitian. Visits were in person prior to March 2020 and virtual afterward. Results Patients' average age was 47.5 years (SD = 12.0) and 73.5% were female. Average weight loss was 14.3% (SD = 6.2%). There was no significant difference in weight loss between virtual and in person programs. Patients on a Glucagon‐like Peptide‐1 Receptor Agonist prior lost less weight. Other significant associations between groups were baseline Hemoglobin A1C, classes attended, as well as the age since peak weight. Conclusion Weight loss from virtual ILI was not significantly different from person ILI. More research is needed to determine how to best stratify care as virtual or in person using FMR programs.